ANALISA PENGARUH IKLIM ORGANISASI DAN KEPRIBADIAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI MOTIVASI (Studi pada Dinas Pendidikan Kota Tegal) (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to examine and analyze whether there was an effect of organizational climate and personality on job satisfaction with the mediation of motivation in Tegal City Department of Education. Sampling method with purposive sampling method. Data is collected by a questionnaire. Tests conducted by the research instrument validity and reliability testing, statistical test equipment being used is multiple regression analysis, R ² test and t-test to test the significance of regression coefficients generated. The results showed that the positive effect of organizational climate on motivation and job satisfaction. Personality positive influence on motivation, but had no effect on job satisfaction. Motivation no effect on job satisfaction Motivation as a mediating variable based on the results of the study can not explain the indirect influence organizational climate and personality on job satisfaction Tegal City Education Department officials. Keywords: organizational climate, personality, motivation and job satisfaction